THE STUDY OF FERTILITY MARINE ECOSYSTEM OF SOUTHEAST SULAWESI BASED ON BACTERIOLOGICAL ASPECT - Djoko Hadi Kunarso (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2011)
The study of waters fertilization in Southeast Sulawesi include Flores Sea, Kabaena Strait, Muna Strait, Buton Strait and Tioro Strait based on bacteriological aspect was conducted on April–May 2006, using the Research Vessel Baruna Jaya VII with total stations 25. The aim of investigation was to find out the total numbers and pattern of distribution heterotrophic bacteria and productivity bacteria in the marine ecosystem of Southeast Sulawesi and related with waters fertilization. The analysis of heterotrophic bacteria was determined based on the Total Plate Count method, whereas bacterial productivity with Acridine Orange Direct Count method. The result indicated that the pattern of distribution and total numbers of heterotrophic bacteria at the surface layers varied between (10–10220)CFU x 10-1/ml with an average 940CFU x 10-1/ml. While at the bottom layer varied between (2–488)CFU x 10-1/ml with an average 91CFU x 10-1/ml. For the bacterial productivity in the form of Carbon biomass at the surface layers varied between (1.30– 5.84) x 10–7grC/m3 with an average 3.56 x 10–7grC/m3, at the bottom layer varied between (0.24–1.33) x 10–7grC/m3 with an average 0.64 x 10–7grC/m3. The result of numbers bacteria that in Southeast Sulawesi waters was lower than the Arafura Sea but still higher than the Aceh Sea. The fluctuation of numbers bacteria perhaps due to the factor of monsoon and environmental was influenced on the marine ecosystem. In general this paper conclude that the condition of marine ecosystem Southeast Sulawesi still relatively fertility.Keywords: Fertility, heterotrophic bacteria, productivity bacteria, Southeast Sulawesi waters